2021
DOI: 10.1097/pai.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Aspartyl (Asparaginyl) β-hydroxylase in NSCLC: Its Diagnostic Value by Means of Exosomes of Bronchoalveolar Lavage

Abstract: The human aspartyl β-hydroxylase (ASPH) is overexpressed in tumor tissues. Bronchoalveolar lavage (BAL) is a diagnostic procedure for infections and malignancies. The aim of this study was to investigate whether tumor exosomes carrying ASPH gene marker were present in bronchoalveolar fluid of patients with non-small cell lung cancer (NSCLC). A tissue microarray analysis was applied to explore the expression of ASPH in different histologic NSCLC. The human NSCLC cell lines and normal bronchial cell lines were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The ASPH and C5orf30 gene products, which were identified as highly significant DEGs in our study, have been identified previously as markers of severe infection [58] . ASPH has also been identified as a marker in various cancers [59] , [60] , [61] , and likely alters Calcium homeostasis [62] . The C5orf30 gene product has been identified as a marker of rheumatoid arthritis severity [63] , [64] , suggesting an effect on cell migration, immunity, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The ASPH and C5orf30 gene products, which were identified as highly significant DEGs in our study, have been identified previously as markers of severe infection [58] . ASPH has also been identified as a marker in various cancers [59] , [60] , [61] , and likely alters Calcium homeostasis [62] . The C5orf30 gene product has been identified as a marker of rheumatoid arthritis severity [63] , [64] , suggesting an effect on cell migration, immunity, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of apoptosis blocking bcl-2 protein predicts a poor prognosis for radiation-treated NSCLC patients [ 84 ]. Bronchoalveolar lavage (BAL)-exosomal human aspartyl β-hydroxylase (ASPH) is a potential biomarker for NSCLC diagnosis [ 85 ].…”
Section: Inhibiting the Synthesis Of Biomoleculementioning
confidence: 99%